UHPLC-ESI-ORBITRAP-MS analysis of the native Mapuche medicinal plant palo negro (Leptocarpha rivularis DC. - Asteraceae) and evaluation of its antioxidant and cholinesterase inhibitory properties - Andrea Jiménez-González; Cristina Quispe; Jorge Bórquez; Beatriz Sepúlveda; Felipe Riveros; Carlos Areche; Edgar Nagles; Olimpo García-Beltrán; Mario J. Simirgiotis (Taylor & Francis Group, 2018)
UHPLC/ESI/MS identification of organic compounds is the first step in the majority of screening techniques for the characterization of biologically active metabolites in natural sources. This paper describes a method for the fast identification and characterisation of secondary metabolites in Leptocarpha rivularis DC. (Palo negro) extracts by HPLC/UV (DAD)-Mass Spectrometry (HPLC/MS). The plant is used for the treatment of several diseases since pre-hispanic Mapuche times. Thirty-seven compounds were detected in the aqueous edible extract for the first time including 4 sesquiterpenes, 10 flavonoids, 9 oxylipins, 2 organic acids, and 11 phenolic acids. In addition, phenolic content antioxidant and cholinesterase inhibitory activities were measured for the first time using the edible infusion. The total polyphenol content of the infusion was 230.76 ± 2.5 mmol GAE/kg dry weight, while the antioxidant activity was 176.51 ± 28.84; 195.28 ± 4.83; and 223.92 ± 2.95 mmol TE/kg dry weight, for the DPPH, ABTS, and FRAP assays, respectively. The cholinesterase inhibitory activity was 7.38 ± 0.03 and 5.74 ± 0.06 mmol GALAE/kg, for the inhibition of acetylcholinesterase AChE and BChE, respectively, showing that this plant is a candidate for the isolation of compounds that can be useful for the treatment of neurodegenerative diseases. Furthermore, this plant could serve also as a raw material for the production of dietary supplements, due to its content of polyphenolic compounds.